"I think I have an addiction too" : narrative analysis of mothers’ experiences in Methamphetamine-affected partnerships : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology, Massey University, New Zealand - Wells, Jesse (Massey University, 2024)
Methamphetamine, a highly addictive stimulant, has become a major global health concern. In New Zealand, methamphetamine is the second most used illicit drug, with per capita usage ranked third highest globally. Although individual impacts are well-documented, the toll on family members is less understood. Substance abuse places a substantial burden on families, impacting their physical, emotional, and financial well-being. Additionally, stigma surrounding substance abuse often discourages families from seeking help, which can worsen the issue. Despite various treatment options in New Zealand, accessing specialized services for methamphetamine addiction remains challenging. Using narrative analysis within a constructivist framework, this research delved into the lived experiences of women in New Zealand as they supported partners struggling with methamphetamine addiction. Four women participated in a semi-structured interview to share their insights into the personal, relational and societal factors influencing their experiences of supporting their partner whilst raising children. The findings underscore the significant mental, physical, emotional, and financial toll on individuals caring for partners with methamphetamine addiction. Caregivers experience anxiety, stress, trauma, and physical distress, alongside emotional turmoil, financial strain, and social isolation, while raising children. The stigma surrounding addiction exacerbates these challenges, limiting access to support services. Societal expectations, particularly gender roles, influence caregiving behaviours, with women often internalizing these roles, leading to co-dependency and difficulty setting boundaries. Emotional labour and societal pressures contribute to burnout, reinforcing unhealthy relational dynamics. The research emphasises the need for systemic solutions, including better access to mental health care, legal protections, and social support. Comprehensive support systems integrating practical resources, therapeutic interventions, and peer support groups are crucial. Legal tools like protection orders and professional support networks are vital for safety and emotional resilience. A collaborative approach involving mental health professionals, addiction specialists, and policymakers is necessary to provide holistic, long-term support for individuals and families affected by addiction.
Keywords: 520302 Clinical psychology